Mainstreaming micro finance - Lalitha, N. (New Delhi, 2003)
The book reviews the progress of micro finance operations in India, analyses the benefit share of women in the total credit off take in the study area under conventional lending, examines the credit delivery system, credit utilization and benefit outflow under micro finance programme and suggests measures for the effective operations of micro finance on the basis of the outcome of the study. The findings of the study are presented in the form of SWOT analysis. The book presents a vivid and penetrating analysis of the micro finance activities at macro as well as micro level, highlights the factors which promote/hinder the micro finance activities, and deals with issues which bear on mainstreaming micro finance activities and promotion of sustainable community based financial system. The also book provides necessary background for understanding the problems faced by NGOS as Micro Finance Institutions and presents policy perspectives. The book contains several innovative initiatives taken by the groups, NGOs and banks and demonstrates how the strategic alliance and partnership among the NGO which acts as MFI, people, banks and government departments should emerge if micro finance has to act as safety net under adverse conditions such as drought and to transform the status of women.
Keywords: Finance, public